2018
DOI: 10.1039/c8ra04886j
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology combined with functional metabolomics discover bile acid metabolism as a promising target for mirabilite against colorectal cancer

Abstract: In this study, a combination of network pharmacology and metabolomics was used to explore the mechanism by which mirabilite regulates bile acid metabolism in the treatment of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 45 publications
(50 reference statements)
1
26
0
Order By: Relevance
“…Biomarkers have become an integral part of the research on diseases. [54][55][56][57][58][59] In this study, it was found that PF regulated 10 biomarkers by the metabolic pathways of phenylalanine, tyrosine and tryptophan biosynthesis, phenylalanine metabolism, and tryptophan metabolism, to achieve a certain therapeutic effect. Although the systematic metabolic analysis was used in our study, we can integrate the physiological indicators and pathological observations to improve this study.…”
Section: Discussionmentioning
confidence: 87%
“…Biomarkers have become an integral part of the research on diseases. [54][55][56][57][58][59] In this study, it was found that PF regulated 10 biomarkers by the metabolic pathways of phenylalanine, tyrosine and tryptophan biosynthesis, phenylalanine metabolism, and tryptophan metabolism, to achieve a certain therapeutic effect. Although the systematic metabolic analysis was used in our study, we can integrate the physiological indicators and pathological observations to improve this study.…”
Section: Discussionmentioning
confidence: 87%
“…[126][127][128][129] Numerous studies have also been tested, including early disease detection, treatment prediction and prognosis, monitoring treatment and recurrence testing. [130][131][132][133][134][135][136][137][138][139] Given the extreme complexity of biological mixtures, most MS analytical methods involve the use of LC, GC or CE. However, rapidly growing applications using evolving separation methods and protocols offer opportunities and challenges.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Gut microbiota participates in the regulation of nutrient hormone signaling processes regulated by bile acids [90].…”
Section: Regulation Of Gut Microbiota On Bile Acidmentioning
confidence: 99%
“…The relationship between bile acids and intestinal fl ora is not unidirectional. Bile acids can alter the structure of the intestinal fl ora by mediating bacterial growth and inhibiting the growth of other sensitive bacteria [90,91,125]. Taurine bile salts, a bile salt hydrolysate,can inhibit a certain dose of C. diffi cile (C. diffi cile) toxins, thereby effectively avoiding damage to colonic epithelial cells [126].…”
Section: Effect Of Bile Acid On Intestinal Fl Oramentioning
confidence: 99%